2018
DOI: 10.1016/j.clinthera.2018.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness Outcomes in Patients With Recurrent or Refractory Head and Neck Cancers: Retrospective Analysis of Data From a Community Oncology Database

Abstract: This study of data from clinical practice shows that there remains a large unmet need for effective therapeutic options in advanced HNC. Patients' characteristics such as alcohol use and performance status were statistically significant predictors of PFS and OS in Stage III-IVc HNC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
1
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
1
1
1
1
Order By: Relevance
“…We did not found that age affects PFS (RR 0.90; 95% CI 0.64–1.25; p = 0.52). This result was consistent with previous studies from Pytynia et al [ 20 ] and Fisher et al [ 21 ]. A reasonable explanation for this was because most patients had no comorbidities and good performance status regardless of their age.…”
Section: Discussionsupporting
confidence: 94%
“…We did not found that age affects PFS (RR 0.90; 95% CI 0.64–1.25; p = 0.52). This result was consistent with previous studies from Pytynia et al [ 20 ] and Fisher et al [ 21 ]. A reasonable explanation for this was because most patients had no comorbidities and good performance status regardless of their age.…”
Section: Discussionsupporting
confidence: 94%
“…This is much longer than other recently published German real-world data from 2011 to 2013 in sample with comparable treatment regimens: 102 patients with probably lower general health status (ECOG performance status ≥ 2: 41%) than in the present study showed a median overall survival of only 7 months (Grunwald et al 2020 ). In contrast, a retrospective data collection of 462 patients from a network of community oncology practices in the United States from 2007 to 2015 on effectiveness of systemic therapy for R/M HNC estimated a median overall survival of 21.0 months, i.e., even longer than in the present study (Fisher et al 2018 ). In contrast, in trials on first-line systemic therapy, typically patients with an ECOG performance status > 1 are not included.…”
Section: Discussioncontrasting
confidence: 74%
“…Our median time to next treatment estimates of 6.1 months pre-IO and 7.4 months post-IO are consistent (marginally longer) than that observed in a prior EMR-based analysis (5.0 months for chemotherapy only treated patients). 24 Our estimates are also longer than the median PFS observed in CheckMate-141: nivolumab-treated ¼ 2.0 months, standard therapy ¼ 2.3 months. 6 Indirect comparison of these results is difficult.…”
Section: Discussionmentioning
confidence: 57%